Notes on Ipomoea (Convolvulaceae) from the Amazonian periphery - Wood, J; Scotland, R (Springer, 2017)
Attention is drawn to the relatively low number of Ipomoea species found in the Amazon basin as well as to the rarity of most species restricted to the region. Six new species from the Amazonian periphery are described: Ipomoea acrensis J. R. I. Wood & Scotland and I. altoamazonica J. R. I. Wood & Scotland from Brazil and Peru, I. maranyonensis J. R. I. Wood & Scotland from Peru, I. macarenaensis J. R. I. Wood & Scotland from Colombia, I. pogonocalyx J. R. I. Wood & Scotland from Brazil and I. deminuta J. R. I. Wood & Scotland from Bolivia. Variation in I. megapotamica is discussed and two subspecies are recognised, subsp. megapotamica from southern South America and subsp. velutina J. R. I. Wood & Scotland from northern Brazil and Venezuela. Plants treated as I. chenopodiifolia M. Martens & Galeotti from Venezuela are recognised as I. retropilosa (Pittier) D. F. Austin. Two subspecies of this species are proposed, subsp. retropilosa being endemic to the Venezuelan Andes whereas the newly described subsp. cundinamarcana J. R. I. Wood & Scotland is restricted to Colombia. I. austinii Infante-Bet. is treated as a synonym of the African I. involucrata P. Beauv., one of a number of Old World species now established in the neotropics.